Pengaruh Likuiditas, Leverage, dan Kinerja Lingkungan terhadap Pengungkapan CSR dengan Moderasi Ukuran Perusahaan pada Perusahaan Pertambangan di Bursa Efek Indonesia - Diana Indah Sri Lestari Pratiwi A; Adiati Trihastuti (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of liquidity, debt level, and environmental performance on the disclosure of Corporate Social Responsibility (CSR), with firm size considered as a moderating variable. The research focuses on mining companies listed on the Indonesian Stock Exchange during the 2022–2024 period. A quantitative research approach was applied using secondary data obtained from annual reports, sustainability reports, and PROPER environmental performance ratings. The sample consisted of 14 mining companies selected through purposive sampling based on specific criteria relevant to the study objectives. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 4 software. The findings reveal that liquidity shows a positive but statistically insignificant relationship with CSR disclosure, indicating that higher liquidity does not necessarily lead to broader CSR reporting. Meanwhile, leverage or debt level does not demonstrate a significant influence on CSR disclosure. In contrast, environmental performance has a positive and significant effect on CSR disclosure, suggesting that companies with better environmental practices tend to communicate their CSR activities more extensively. Furthermore, firm size does not moderate the relationship between liquidity, debt level, environmental performance, and CSR disclosure.